A review on ASEAN-Australia education dialogue: so close yet so far - Muhizam Mustafa, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The relationship between ASEAN and Australian which began in 1974 as a regional cooperation under the AusAID program to promote cooperation between Australia and Southeast Asia. Since then new initiative by Australian government especially in the educational mobility sector to bridge the relationship with ASEAN with the introduction of the New Colombo plan and the Endeavour Leadership program (2019-2020) - two-way mobility for short and long-term study, research and professional development with Australia’s priority partner countries. This effort provides opportunities for established and emerging leaders to undertake a global mobility experience within their study, research or professional field. This program is also developed to strengthen the cultural-economic immersion- which is seen as the driving force, as a leaders-led forum for dialogue and cooperation on broad strategic, political and economic issues of common interest and concern with the aim of promoting peace, stability and economic prosperity and cultural integration in the region. However, despite the effort, Australian- ASEAN mobility relationship is relatively low in comparison to ASEAN-ASEAN and ASEAN-EU mobility traffic. This paper looks at the issue pertaining to the student mobility between ASEAN and Australia and within ASEAN and the effort by Australian government in addressing the issue of the student mobility cooperation between ASEAN and Australia.